Mismatch between indigenous ghanaian and hindu-arabic systems in didactising counting and place value - ALI, Clement Ayarebilla (Acta Didactica Napocensia, 2023)
"Studies show that indigenous languages have exhibited enormous impact on the evolution and didactics of counting and place value. However, Ghana systems have different perspectives and pose varied successes on the didactics of counting and place value. In this study, we explored a mixed methods design to examine the mismatch between Ghanaian and HinduArabic systems. With a sample of 178 participants, we further examined not only student-teachers’ knowledge and transitioning but also their skills and conceptualisation in didactising nine Ghanaian languages with respective to the Hindu-Arabic system. Both quantitative and qualitative data were collected through test and interview instruments. They were analysed by utilising T-test, ANOVA and verbal narratives which complemented and corroborated each other. The one-sample t-test result indicates that there was no impact of Ghanaian languages on counting and place value systems. However, the ANOVA test result infers that there is an impact of indigenous Ghanaian language on counting and place value systems. The qualitative results confirmed that the studentteachers had average skills in didactising counting and place value systems in the Ghanaian indigenous languages. It was therefore recommended, among other things that, measures should be taken not only to synchronise the Ghanaian languages but also to finetune the languages in tandem with the Hindu."